Motor activity affects adult skeletal muscle re‐innervation acting via tyrosine kinase receptors. Issue 9 (3rd February 2013) - Sartini, Stefano; Bartolini, Fanny; Ambrogini, Patrizia; Betti, Michele; Ciuffoli, Stefano; Lattanzi, Davide; Di Palma, Michael; Cuppini, Riccardo
Abstract Recently, muscle expression of brain‐derived neurotrophic factor (BDNF) mRNA and protein under activity control has been reported. BDNF is a neurotrophin known to be involved in axon sprouting in the CNS. Hence, we set out to study the effect of chronic treadmill mid‐intensity running on adult rat muscle re‐innervation, and to explore the involvement of BDNF and tropomyosin‐related kinase (Trk) receptors. After nerve crush, muscle re‐innervation was evaluated using intracellular recordings, tension recordings, immunostaining and Western blot analyses. An enhanced muscle multiple innervation was found in running rats that was fully reversed to control values blocking Trk receptors or interrupting the running activity. An increase in muscle multiple innervation was also found in sedentary rats treated with a selective TrkB receptor agonist. The expression of TrkB receptors by intramuscular axons was demonstrated, and increased muscle expression of BDNF was found in running animals. The increase in muscle multiple innervation was consistent with the faster muscle re‐innervation that we found in running animals. We conclude that, when regenerating axons contact muscle cells, muscle activity progressively increases modulating BDNF and possibly other growth factors, which in turn, acting via Trk receptors, induce axon sprouting to re‐innervate skeletal muscle.